Forecasting Layer Egg Production as Animal Source Food for Protein to Reduce Stunting in West Java, Indonesia - Kalinaki, Hanifar; Sukandar, Dadang (Media Gizi Indonesia, 2024)
Stunting still becomes a global public health challenge affecting millions of people, including Indonesians. To alleviate the situation, Indonesia is fighting to reduce the prevalence of stunting to 10.4% in 2024 by increasing the consumption of Animal Source Foods. This study aimed to forecast the Layer Egg Production in West Java, Indonesia, as an animal source food to provide protein for reducing stunting. The study employed descriptive quantitative and time series approaches using secondary data analysis. The Layer Egg Production for 2023-2025 was forecasted using the Moving Average (MA) and Weighted Moving Average (WMA) using Layer Egg production data for 2000-2022. The WMA method was more accurate as it had a Mean Absolute Percentage Error (MAPE) of 15.32 compared to a MAPE of MA of 16.23. Furthermore, the population projections for West Java 2021-2025 were made by the Geometric method. The study's findings declare that the Layer Egg Production is still low to meet the population demand for West Java. In this case, the population can get 18.77 g of egg per person daily, an average of 2.4g of protein. In addition, the egg contributes 4.2% to the protein required by each person a day.